Formación profesional y su incidencia en los estudiantes de Secretariado Ejecutivo Bilingüe de la Universidad Técnica de Babahoyo - Sala Zuñiga, Lixsy Angeline (2022)
The objective of this study is to define the professional competencies and the impact on the bilingual executive secretarial students of the Technical University of Babahoyo (UTB), taking into account the learning deficiencies of the students of the institution who do not feel able to perform their functional roles within the work areas in which they will exercise. Therefore, new pedagogical techniques have been generated with the aim of improving the learning of their students, although these shortcomings and lack of knowledge do not arise in recent years, from the beginning the lack of knowledge or preparation does not fall only on teachers but also on students who do not seek to inculcate themselves in a broader way. In the investigative context, relevant topics of the theoretical support were approached in a bibliographic-documental way that allowed us to know in depth the evolution of education and its educational processes, as well as the importance of this career and its methodology of study in labor relations. Finally, for the development of this research the methods used were the inductive, which provided to know more about the education that is granted within the institution and the deductive because it determined the next functions to be performed by professionals and establish relevant conclusions based on the information obtained, this response will support the content of a questionnaire of ten questions that were made to students of Bilingual Secretariat of the Technical University of Babahoyo, according to the current academic period.